China’s Fiscal and Monetary Policies During the Global Financial Crisis and the Covid-19 Pandemic: Lessons and Policy Implications - Trương Quang Thông (Contemporary Chinese Political Economy and Strategic Relations: An International Journal)
Using statistical and institutional analysis approaches, this study seeks to make a comprehensive study on fiscal and monetary policies and tools adopted by China for ensuring and sustaining its economic development despite the 2008 Global Financial Crisis (GFC) and the Covid-19 pandemic. Primarily, it aims to find evidence on the more appropriate fiscal and monetary policies and tools, specifically by giving emphasis to those implemented by the Chinese government to stimulate and sustain economic development, particularly during the earlier mentioned contexts. The study generated the following major findings: First, the transition from loosening monetary policy to tightening monetary policy at the time of 2008 GFC is one notable approach and a valuable lesson learned; Second, prioritization of lifesaving and enhancing economic resiliency should be at the core in addressing the economic challenges, particularly during the Covid-19 epidemic; and Third, the importance of the central bank to function as a transmission belt for government to flood the country with liquidity through commercial bank lending.